DESIGN REVIEW WITH CLIMATE SENSITIVE URBAN DESIGN APPROACH Case Study: Terminal Terpadu Gedebage - Sugangga, Marisa
Design review is applied to improve the quality of a design either building, city, or landscape. The quality of design can be improved in accordance with the objectives to be achieved using the appropriate approach. One approach that focuses on sustainable development is climate response that can be achieved through the concept of climate sensitive urban design. This concept is one of the urban design approach that uses the climate context as the main criteria in the design. The development of a new Bandung city center in Gedebage can be one of the triggers of temperature rise on the surface of urban heat island. This can lead to reduced thermal comfort in the area. The issue can be detected early by using a design review on the Rencana Tata Bangunan dan Lingkungan (RTBL) document. This research will conduct a design review with climate sensitive urban design approach by formulating design principles that give attention to climate as the main element of design. Using the ENVI-Met simulation tool, it was found that by adding CSUD design principles, the quality of microclimate in the area would improve. The initial recommended recommendations are to reduce the height of the building, increase the open space, and replace the material. The conclusion of this research is the design of Terminal Terpadu Gedebage Teknopolis is in the category of comfortable by tropical country standard.